1993
DOI: 10.3928/1081-597x-19930302-21
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapeutic Keratectomy: Long-Term Results in 166 Eyes

Abstract: One hundred sixty-six eyes with corneal disease were treated with the excimer laser in order to ablate opacities, irregularities, or to improve wound healing. Postoperative follow up time was 15 months (range 6 to 28 months). An individual goal was set for each patient and 84% achieved the goal. The visual acuity change is given for each subgroup. Phototherapeutic keratectomy (PTK) was shown to be an advantageous surgical method, where the success is in the careful preoperative evaluation. One problem with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…But most complications were completely reversible during follow-up, and only a minority resulted in a permanent corneal haze. Nine studies [11, 19‒24, 28, 30] reported spherical equivalent manifest refraction change after PTK (Fig. 8), among which 5 publications [11, 21‒24] indicated a slight trend toward mild hyperopia with an overall incidence of 20% (95% CI, 11%–28%), while other four studies reported no significant change in apparent refraction after PTK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But most complications were completely reversible during follow-up, and only a minority resulted in a permanent corneal haze. Nine studies [11, 19‒24, 28, 30] reported spherical equivalent manifest refraction change after PTK (Fig. 8), among which 5 publications [11, 21‒24] indicated a slight trend toward mild hyperopia with an overall incidence of 20% (95% CI, 11%–28%), while other four studies reported no significant change in apparent refraction after PTK.…”
Section: Resultsmentioning
confidence: 99%
“…After eliminating nonrelevant articles by title and abstract screening, 71 articles were included for full-text screening. Twenty-one studies were included in our qualitative and quantitative analyses [11‒14, 16‒30], including 4 controlled experiments and 17 single-arm experiments. The intervention method was PTK, and the control was DB [5], PTK + peripheral anterior stromal puncture (ASP) [12], ED + ASP and ED + DB [11], or alcohol delamination [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Previous studies have evaluated the safety and efficacy of excimer laser PTK for the treatment of anterior corneal opacities and surface irregularities. [15][16][17] Excimer laser PTK has been used to treat persistent adenoviral subepithelial corneal opacities with positive results. The 193nm Argon-Fluoride laser photochemically breaks intermolecular bonds, expelling corneal tissue in a controlled manner without causing collateral thermal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported some degree of induced hyperopia of about 1.52D as measured 12 months post-op. 17 Stark et al have described great variability in the refractive changes following stromal ablations greater than 85μm. 18 A thinner ablation induces a smaller hyperopic shift.…”
Section: Discussionmentioning
confidence: 99%